2012
DOI: 10.3892/mco.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk of recurrent colorectal neoplasia with Helicobacter pylori-associated chronic atrophic gastritis: A follow-up study of patients with endoscopically resected colorectal neoplasia

Abstract: Abstract.In a previous population-based case-control study, we demonstrated an elevated risk of colorectal neoplasia with Helicobacter pylori (H. pylori) infection. The present study investigated the effects of H. pylori-associated chronic gastritis on the development of colorectal neoplasia by analyzing the recurrence of colorectal neoplasia subsequent to endoscopic resection. Ninety-nine patients who had undergone endoscopic resection of colorectal neoplasia were monitored under colonoscopy, and the recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Even though some studies did not find an association, the positive correlation of H. pylori and colonic neoplasia was strengthened by a recent study including a large number of patients, in which various forms of gastritis related to H. pylori consistently increased the risk for colonic neoplasms . Recently, another interesting study demonstrated that patients with H. pylori ‐induced atrophic gastritis are at an increased risk for the recurrence of colorectal neoplasia after endoscopic resection . The small number of patients with colorectal cancer or adenomas with high grade neoplasia in our study did not permit an interpretation of this group of patients and thus a solid conclusion on the absence of an association between H. pylori infection and colorectal cancer or adenomas with high grade neoplasia cannot be given.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Even though some studies did not find an association, the positive correlation of H. pylori and colonic neoplasia was strengthened by a recent study including a large number of patients, in which various forms of gastritis related to H. pylori consistently increased the risk for colonic neoplasms . Recently, another interesting study demonstrated that patients with H. pylori ‐induced atrophic gastritis are at an increased risk for the recurrence of colorectal neoplasia after endoscopic resection . The small number of patients with colorectal cancer or adenomas with high grade neoplasia in our study did not permit an interpretation of this group of patients and thus a solid conclusion on the absence of an association between H. pylori infection and colorectal cancer or adenomas with high grade neoplasia cannot be given.…”
Section: Discussioncontrasting
confidence: 76%
“…patients with H. pylori-induced atrophic gastritis are at an increased risk for the recurrence of colorectal neoplasia after endoscopic resection. 25 The small number of patients with colorectal cancer or adenomas with high grade neoplasia in our study did not permit an interpretation of this group of patients and thus a solid conclusion on the absence of an association between H. pylori infection and colorectal cancer or adenomas with high grade neoplasia cannot be given.…”
Section: Infectious Causes Of Cancermentioning
confidence: 63%
“…A total of 6 of the 295 polyps were incompletely excised, with residual adenomatous or carcinomatous tissue in the incision margin (2.03% of all polyps). The rate of single resection was 97.97%, which is similar to that in relevant reports[ 21 ]. Failed endoscopic resection of colorectal polyps is related to a number of factors, which can be summarized as follows: 1) operator skill—those who have a preliminary mastery of EMR fail to perform endoscopic resection proficiently; 2) inadequate exposure of the endoscopic polyps—a variety of factors such as overly large polyps, inadequate intestinal preparation, and poor polyp location can lead to inadequate exposure of endoscopic polyps and a limited field of view; and 3) underestimation of the submucosal depth of the polyps, especially for polyps > 2 cm in diameter and Yamada type II and lateral growth polyps, whose histology can invade the muscle and even the plasma membrane layer, rendering EMR impossible[ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is indicated that the recurrence rate of helicobacter pylori eradication group was more lower than helicobacter pylori no eradication group. This shows that helicobacter pylori eradication can signi cantly decrease the recurrent risk of colonic polyp,which indicated that helicobacter pylori eradication may be the effective approache to prevent the recurrence of colonic polyp [12,13].…”
Section: Discussionmentioning
confidence: 87%